Curcumin-guided nanotherapy: a lipid-based nanomedicine for targeted drug delivery in breast cancer therapy. (3rd May 2016) - Lin, Mingzhen; Teng, Lili; Wang, Yang; Zhang, Jiaxin; Sun, Xianglian
Abstract: Background : Delivery of anti-cancer drugs into the cancer cells or tissues by multifunctional nanocarriers may provide a new paradigm in cancer treatment. In this study, folate (FA) decorated nanostructured lipid carriers (NLCs) were constructed as nanomedicine for the delivery of curcumin (CUR). Methods : CUR-loaded NLCs (CUR-NLCs) were prepared. FA containing polyethylene glycol (PEG)-distearoylphosphatidylethanolamine (DSPE) (FA-PEG-DSPE) was synthesized and used for the decoration of CUR-NLCs. Their particle size, zeta potential, and drug encapsulation efficiency (EE) were evaluated. In vitro cytotoxicity study FA decorated CUR-NLCs (FA-CUR-NLCs) was tested in MCF-7 human breast cancer cells (MCF-7 cells). In vivo anti-tumor efficacies of the carriers were evaluated on mice bearing breast cancer model. Results : The optimum FA-CUR-NLCs formulations with the particle size of 127 nm and with a +13 mV surface charge. The growth of MCF-7 cells in vitro was obviously inhibited. FA-CUR-NLCs also displayed the best anti-tumor activity than other formulations in vivo . Conclusion : The results demonstrated that FA-CUR-NLCs were efficient in selective delivery to cancer cells over-expressing FA receptors (FRs). Also FA-CUR-NLCs transfer CUR to the breast cancer cells, enhance the anti-tumor capacity. Thus, FA-CUR-NLCs could prove to be a superior nanomedicine to achieve tumor therapeutic efficacy.